Proton radiotherapy for recurrent or metastatic sarcoma with palliative quad shot. (4th June 2021) - Lee, Anna; Kang, Jung J.; Bernstein, Havah; Marqueen, Kathryn E.; Neal, Brian; Kelly, Ciara M.; Dickson, Mark A.; Jillian Tsai, Chiaojung; Tap, William; Singer, Samuel; Alektiar, Kaled; Lee, Nancy Y.
Abstract: Patients with previously treated, recurrent or metastatic sarcomas who have progressed on multiples lines of systemic therapy may have limited options for local control. We evaluated outcomes of palliative proton therapy with the quad shot regimen to unresectable disease for patients with recurrent and/or metastatic sarcoma. From 2014 to 2018, 28 patients with recurrent or metastatic sarcomas were treated to 40 total sites with palliative proton RT with quad shot (14.8 Gy/4 twice daily). Outcomes included toxicity, ability to receive further systemic therapy, and subjective palliative response. Univariate analysis was performed for local progression‐free survival (LPFS) and overall survival (OS). Of the 40 total sites, 25 (62.5%) received ≥3 cycles with median follow up of 12 months (IQR 4–19). The most common histologies were GIST (9; 22.5%) and leiomyosarcoma (7; 17.5%). A total of 27 (67.5%) sites were located in the abdomen or pelvis. Seventeen (42.5%) treatments involved concurrent systemic therapy and 13 (32.5%) patients received further systemic therapy following proton therapy. Overall subjective palliative response was 70%. Median LPFS was 11 months and 6‐month LPFS was 66.1%. On univariate analysis, receipt of four cycles of quad shot (HR 0.06, p  = 0.02) and receipt of systemic therapy after completion of radiation therapy (HR 0.17, p  = 0.02) were associated with improved LPFS. Three grade 3 acute toxicities were observed. The proton quad shot regimen serves as a feasible alternative for patients with previously treated, recurrent or metastatic sarcomas where overall treatment options may be limited. Abstract : Patients with previously treated, recurrent or metastatic sarcomas who have progressed on multiple lines of systemic therapy have limited options for local control. We report on 28 patients treated to 40 sites with proton therapy using the quad shot regimen and found subjective palliative response rate of 70% and median LPFS of 11 months with little toxicity.